2020
DOI: 10.1186/s12951-020-0585-9
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of minocycline-loaded PLGA nanoparticles from gelatin-coated neural implants attenuates acute brain tissue responses in mice

Abstract: Background: Neural interfaces often elicit inflammatory responses and neuronal loss in the surrounding tissue which adversely affect the function and longevity of the implanted device. Minocycline, an anti-inflammatory pharmaceutics with neuroprotective properties, may be used for reducing the acute brain tissue responses after implantation. However, conventional administration routes require high doses which can cause adverse systemic side effects. Therefore, the aim of this study was to develop and evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…At the same time, the high cost and inactivation of BMPs limit their extensive use in bone repair. It has been reported that nanoparticles (NPs) produced from poly (lactic acid-co-glycolic acid) (PLGA) [10][11][12], poly (L-lactic acid) (PLA) [13][14][15] and polycaprolactone (PCL) [16][17][18] can release recombinant human BMP2 or BMP7. Nevertheless, these BMPs only increased alkaline phosphatase (ALP) activity for a short time.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the high cost and inactivation of BMPs limit their extensive use in bone repair. It has been reported that nanoparticles (NPs) produced from poly (lactic acid-co-glycolic acid) (PLGA) [10][11][12], poly (L-lactic acid) (PLA) [13][14][15] and polycaprolactone (PCL) [16][17][18] can release recombinant human BMP2 or BMP7. Nevertheless, these BMPs only increased alkaline phosphatase (ALP) activity for a short time.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are commonly used as part of post-surgery treatments and have been investigated acutely in mice, showing a bene cial reduction of glial encapsulation post-implantation of MEAs [51][52][53] . However, it is unlikely that regular antibiotic treatment throughout the duration of microelectrode implantation would represent a practical clinical solution to improved microelectrode performance.…”
Section: Discussionmentioning
confidence: 99%
“…[102] Mechanical sensitivity by neurons has also been demonstrated, however, the exact implications are unknown. [27,157] The soma can withstand some compressive disturbance [42,43,123,158] as evidenced by histological examination, however, reports indicate that mechanical disruption can significantly alter neuronal spike dynamics. [157,159] As early as 1970, Humphrey suggested that improved neural SU recording performance using individually advanceable microelectrode arrays could be achieved when insertion-induced tissue compression was allowed to resolve before final electrode positioning.…”
Section: Mechanical Forces Experienced By Tissuesmentioning
confidence: 99%